A Modified Nelder-Mead Algorithm for Photovoltaic Parameters Identification - Mesbahi, Oumaima (2022)
Photovoltaic panels are prone to degradation after long outdoor exposure, which can be manifested in multiple forms. This phenomenon also causes an alteration of the panel’s parameters. In this work, a heuristic search methodology based on the Nelder-Mead algorithm is applied in the estimation of photovoltaic panel parameters. Modifications that improve the performance of the method are also presented. The results of this modified Nelder-Mead algorithm are compared with the results of the classical method. A sensitivity analysis towards additive noise and ADC resolution is performed.